RELIGIOUS AND CULTURAL HARMONIES IN THE ART OF MASAMPER - Abu Muslim (Analisa: Journal of Social Science and Religion, 2016)
This paper tries to track a potential religious harmony through a local tradition namely the art of Masamper in Sangir community. This study uses a qualitative- descriptive method to reveal the religious aspect in Art Masamper by first doing a study observations of implementation art in society, to further explore the values of divinity contained in Masamper process, to keep watching the dialectic of art and religion that were rolling. As one of the cultural-religious studies, this study is not an experimental research seeking a rule, but an interpretive research that searches for meaning. So that any meaning contained in the overall aspect of Masamper (processes, and religious dialectic of culture) becomes the point of analysis obtained from the observation, in-depth interviews, and a review of literatures related to discourse analysis. The results showed that Masamper as one of the remains of the ancestral cultural arts in Sangir society, other than as a means of proselytism, it also becomes one of the adhesives socio-religious harmony in North Sulawesi. Masamper can dilute the differences in beliefs into a cultural engagement through art performances which invites the public to appreciate each other in the name of culture and mutual respect in the practice of religious beliefs.